21st Century Robot - Johnson, Brian David (Maker Media, 2014)
When companies develop a new technology, do they ask how it might affect the people who will actually use it? That, more or less, sums up Brian David Johnson's duties as Intel's futurist-in-residence. In this fascinating book, Johnson provides a collection of science fiction prototyping stories that attempt to answer the question. These stories focus on the same theme: scientists and thinkers exploring personal robotics as a new form of artificial intelligence. This isn't fanciful speculation. Johnson's stories are based on Intel's futurecasting research, which uses ethnographic field studies, technology research, trend data, and science fiction to develop a pragmatic vision of consumers and computing. 21st Century Robot presents science fiction designed to bring about science fact. Get real insight into technology and the future with this book. It will open your eyes.
Includes index. - Print version record
Keywords: Science fiction; Storytelling; Future, The, in literature; Art de conter; Futur dans la littérature; TECHNOLOGY & ENGINEERING; Engineering (General)